Regulatory reform of land acquisition for public interest after the omnibus law on job creation - Muhammad Rifaldi Setiawan; Ayang Afira Anugerahayu (Priviet Social Sciences Journal, 2025)
Land acquisition for public interest constitutes a fundamental aspect of national development; however, it frequently generates conflicts owing to the tension between development objectives and the protection of community rights. Prior to the enactment of Law Number 11 of 2020 on Job Creation, the legal framework governing land acquisition was regulated by Law Number 2 of 2012, which, despite providing a comprehensive statutory basis, continued to face obstacles, including lengthy procedures, high costs, and dissatisfaction with the compensation determination process. The enactment of the Job Creation Law introduced significant changes through the simplification of procedures, expansion of the definition of public interest, strengthening of institutional mechanisms, digitization of processes, and introduction of the land bank concept. This new regulation aims to accelerate infrastructure development while safeguarding community rights through more flexible compensation mechanisms and effective dispute resolution processes. However, these reforms raise concerns about a potential reduction in protection for vulnerable groups due to procedural acceleration. This study employs a normative and conceptual approach, drawing on statutory analysis and legal doctrine to assess the implications of the new regulatory framework. The findings indicate that although the Job Creation Law enhances the efficiency of land acquisition, the success of its implementation ultimately depends on the quality of on-the-ground execution, strict oversight, and the active participation of affected communities in the decision-making process.